PERFORMANCE ANALYSIS OF EMPLOYEE FUNCTIONAL POSITION ANALYST STAFFING IN THE PROVINCIA SECRETARIAT WEST KALIMANTAN - Maulidiya, Tisca - (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
The lack of optimal performance of employees holding the Functional Position of Personnel Analyst within the Regional Secretariat of West Kalimantan Province has prompted the author to conduct a study. The main problem in this study is to analyze the factors that support the increase in the performance of Employees in the Functional Position of Personnel Analyst in the Regional Secretariat of West Kalimantan Province. Personnel within the Regional Secretariat of West Kalimantan Province. This research is a descriptive qualitative research. The results of this study indicate that these three factors have benefits for improving employee performance. The average employee for the Functional Position of Personnel Analyst at the Regional Secretariat of West Kalimantan Province has the ability to work because of the length of experience and tenure of service. Employees of the Functional Personnel Analyst Position at the Regional Secretariat of the Province of West Kalimantan have good work motivation because of the TPP (Additional Employee Income), but the performance of employees of the Functional Position of Personnel Analyst at the Regional Secretariat of the Province of West Kalimantan is weakened due to minimal or inadequate work facilities.that involves effective community and government participation .Keywords: Employee performance, work ability, motivation and work facilities.